2019
DOI: 10.1177/2378023119845740
|View full text |Cite
|
Sign up to set email alerts
|

Intracohort Trends in Ethnic Earnings Gaps: The Role of Education

Abstract: This study demonstrates that studying ethnic/racial inequality on the basis of cross-sectional data conceals how such inequality might unfold over the life course. Moving beyond a snapshot perspective, we ask, Do Israel's Jewish ethnic groups differ in their long-term earnings trajectories? Analyzing nearly 20 years of registered earnings data, the authors find that for the same cohort (25-to 32-year-old Jews in 1995), the ethnic earnings gap has widened over these years. This trend, we demonstrate, is explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…As in the previous analysis, we apply multi-level models in which person-age is nested in individuals, estimating earnings trajectories in each educational path for men and women separately. Since recent scholarship has shown that the earnings trajectories of the two Jewish groups have fanned out over the life course 10 , but that the returns to education are also identical for both sub-populations (Yaish and Gabay-Egozi, 2019), we have included in our model two-way interaction terms between ethno-religious groups and age and ethno-religious groups and age 2 to capture this fanning out trend. This model, then, explores the possibility that the three ethno-religious groups share similar returns to educational paths (the three-way interaction terms-ethno-religious group, path, age-did not reach an acceptable statistically significant level for either men or women), but that earnings inequality between the ethnoreligious groups changes, as suggested by Yaish and Gabay-Egozi (2019).…”
Section: Resultsmentioning
confidence: 99%
“…As in the previous analysis, we apply multi-level models in which person-age is nested in individuals, estimating earnings trajectories in each educational path for men and women separately. Since recent scholarship has shown that the earnings trajectories of the two Jewish groups have fanned out over the life course 10 , but that the returns to education are also identical for both sub-populations (Yaish and Gabay-Egozi, 2019), we have included in our model two-way interaction terms between ethno-religious groups and age and ethno-religious groups and age 2 to capture this fanning out trend. This model, then, explores the possibility that the three ethno-religious groups share similar returns to educational paths (the three-way interaction terms-ethno-religious group, path, age-did not reach an acceptable statistically significant level for either men or women), but that earnings inequality between the ethnoreligious groups changes, as suggested by Yaish and Gabay-Egozi (2019).…”
Section: Resultsmentioning
confidence: 99%
“…Income inequality, in some respects, is visible in the field of education as well. Studies (e.g., Yaish & Gabay‐Egozi, 2019) show that inequality in education brings inequality in earnings that hinder a country's growth. Thus, like other multiracial countries, Malaysia should focus on such education where every individual disregard of their ethnicity will freely enjoy equal opportunity.…”
Section: Resultsmentioning
confidence: 99%
“…However, such a trend of income inequality is on an upward trajectory. The empirical study of Yaish and Gabay‐Egozi (2019) finds that in Israel, the earning gap among the ethnic group has been in ascending order, though the study of Ravallion (2018) says that overall income inequality in the international context is in descending direction in the recent years. Income inequality refers to economic inequality that reflects in political and social inequality too.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The Educational Review, USA religious community, which denies them an equal position. Their status rises not only within their own family, but also within their communities-even within Jewish and Muslim orthodox religious communities, which are quite determined to exclude women from sources of power (Aish & Gabay-Egozi, 2019;Khurshid, 2019;Neal, 2014). The significant differences in gender empowerment found between Jews and Muslims, with higher rates among Muslims, and between non-religious and religious women, and also with higher rates among religious women, can be explained by the fact that non-religious students, by opting for higher education, marked the beginning of their gender empowerment, completing the entire process during their studies.…”
Section: Discussionmentioning
confidence: 99%